2016
DOI: 10.5535/arm.2016.40.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Cutoff Value for Ultrasonography of the Common Fibular Neuropathy at the Fibular Head

Abstract: ObjectiveTo establish the diagnostic cutoff value of ultrasonographic measurement for common fibular neuropathy (CFN) at the fibular head (FH).MethodsTwenty patients with electrodiagnostically diagnosed CFN at the FH and 30 healthy controls were included in the study. The cross-sectional area (CSA) of sciatic nerve at mid-thigh level, common fibular nerve at popliteal fossa (PF), and common fibular (CF) nerve at FH were measured. Additionally, the difference of CF nerve CSA at the FH between symptomatic side a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 27 publications
5
32
0
3
Order By: Relevance
“…Recently, Kim et al described a cutoff value of 0.117 cm 2 with sensitivity of 85% and specificity of 90%, which is very close to our findings (8). The reason for relatively high specificity in our study could be the lower number of patients and extreme enlargement seen in a large percentage of them.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, Kim et al described a cutoff value of 0.117 cm 2 with sensitivity of 85% and specificity of 90%, which is very close to our findings (8). The reason for relatively high specificity in our study could be the lower number of patients and extreme enlargement seen in a large percentage of them.…”
Section: Discussionsupporting
confidence: 89%
“…The reason for relatively high specificity in our study could be the lower number of patients and extreme enlargement seen in a large percentage of them. Kim et al noted that comparing the difference between the symptomatic side with the asymptomatic side or calculating the ratio would be helpful in diagnosis of PNFH (sensitivity 83% and 72%, specificity 97% and 97%) (8). When comparing the asymptomatic side with controls, we noted no significant difference in CSA measurements and found it unnecessary to compare differences between symptomatic sides and asymptomatic sides.…”
Section: Discussionmentioning
confidence: 51%
“…They provided fibular head CSA measurements in women of 10 ± 3 mm 2 and in men of 12 ± 4 mm 2 ( P = .031) . A year later, Kim et al concluded the cut‐off value of ultrasonographic measurement for FN at the fibular head to be 11.7 mm 2 , using the asymptomatic contralateral side as a control . In this study we aimed to determine the diagnostic value of a CSA ratio by comparing measurements at the fibular head and the popliteal fossa.…”
Section: Introductionmentioning
confidence: 95%
“…9 A year later, Kim et al concluded the cut-off value of ultrasonographic measurement for FN at the fibular head to be 11.7 mm 2 , using the asymptomatic contralateral side as a control. 10 In this study we aimed to determine the diagnostic value of a CSA ratio by comparing measurements at the fibular head and the popliteal fossa. Specific ultrasound data compiled included fibular nerve CSA measurements at the fibular head and popliteal fossa of both limbs from each patient.…”
Section: Introductionmentioning
confidence: 99%
“…In letzter Zeit gewann daher die direkte Visualisierung der Nerven mittels hochauflösendem Ultraschall zunehmend an Bedeutung. Hierdurch lassen sich Rückschlüsse auf eine mögliche Kompression ziehen [2, 3, [24][25][26].…”
Section: Diskussionunclassified